Interaction between the elements characterizing the forced and parametric excitations - Dao, Nguyen Van (Vietnam Journal of Mechanics, 1998)
In nonlinear systems, the first order of smallness terms of nonresonance forced and parametric excitations have no effect on the oscillation in the first an approximation. However, they do interact one with another in the second approximation.Using the asymptotic method of nonlinear mechanics [1] we obtain the equations for the amplitudes and phases of oscillation. The amplitude curves are drawn digital computer. The stationary oscillations and their stability are of special interest.